(untitled) (Pedagogy of Higher and Secondary Education, 2006)
In article problems sense-formed concepts "a category of integration" in a context of globalization and differentiation of vocational training of the teacher of music of a polyart structure are considered Mechanisms of integration are analyzed in view of projective technologies of diagnosing of individual opportunities of the teacher of music. Integrative mechanisms are considered in a context of interaction of principles of the concentrated plural influence, overlapping, replacement of functions with philosophical culiuralogikal, the psycho-pedagogical art criticism points of view. The variant integrative is offered to the semantic model, synthesizing initial images with modem scientific-art representations.